1976
DOI: 10.1007/bf00609463
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment with ?-blockers after myocardial infarction

Abstract: 162 patients discharged from hospital after mycardial infarction were randomly allocated to two groups, one received alprenolol 400 mg daily and the other served as the control. The period of follow-up was two years and all other treatment given was standardized. The two groups did not differ with respect to risk factors for myocardial infarction, the course of the acute infarct or treatment during follow-up. After two years one patient in the group treated with alprenolol had died suddenly as compared to nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…These findings support the results of earlier trials with alprenolol (Wilhelinsson et al, 1974;Ahlmark & Saetre, 1976;Andersen et al, 1979) and practolol (Green et al, 1975) and recently published trials with timolol (Norwegian Multicenter Study Group, 1981), metoprolol (Hjalmarson et al, 1981), and propranolol (Beta-blocker Heart Attack Study Group, 1981).…”
Section: Commentsupporting
confidence: 85%
“…These findings support the results of earlier trials with alprenolol (Wilhelinsson et al, 1974;Ahlmark & Saetre, 1976;Andersen et al, 1979) and practolol (Green et al, 1975) and recently published trials with timolol (Norwegian Multicenter Study Group, 1981), metoprolol (Hjalmarson et al, 1981), and propranolol (Beta-blocker Heart Attack Study Group, 1981).…”
Section: Commentsupporting
confidence: 85%
“…Previous studies have demonstrated that pure p-adrenoceptor antagonists, such as propranolol, can reduce infarct size in ani mals [3,13,25], and can reduce mortality in humans after acute myocardial infarction [6,8,10,11,26,27], However, the effect of the new multiple action drug, carvedilol, in re ducing infarct size following coronary artery occlusion has not yet been established. One might assume that due to the P-adrenoceptor blocking activity of the drug, carvedilol, like propranolol, would display a cardioprotec tive effect in animal models during acute myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…The cardiopro tective effects of p-adrenoceptor antagonists have been clearly demonstrated in animals [ 1 -3] as well as in humans [4][5][6] where these drugs have been shown to reduce mortality following acute myocardial infarction and to prevent reinfarction [7][8][9][10][11]. It is generally believed that the cardioprotective effects of P-adrenoceptor antagonists result from an improvement in the balance between myo cardial oxygen supply and demand by reduc ing myocardial work, which occurs second ary to reductions in both heart rate and con tractility.…”
Section: Introductionmentioning
confidence: 99%
“…Beta-adrenergic block ing drugs like propranolol that can relieve angina and decrease heart rate may have great potential value in preventing life-threatening rhythm prob lems. Clinical trials undertaken in Sweden and England have suggested that there may be value in using the beta-blocking drugs, alprenolol and prac tolol (13,14). Unfortunately, the studies were not conclusive because of their small size, side effects, and other problems: thus no defi nitive informa tion is available.…”
Section: New Drugs Surgical and Diagnostic Techniquesmentioning
confidence: 99%